Pengaruh Gaya Kepemimpinan dan Disiplin Kerja Terhadap Kinerja Pegawai Kantor Kecamatan Rajeg Kabupaten Tangerang - Rahmawati, Umi; H, Herayati; Windasari, Vicky (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
In the current era of globalization, every institution is expected to optimize employee performance to effectively achieve organizational objectives. This study aims to examine the influence of leadership style and work discipline on employee performance at the Rajeg District Office, Tangerang Regency. The research adopts a descriptive quantitative approach, with data collected through questionnaires and analyzed using SPSS. A total of 50 respondents were selected using a saturated sampling technique. The analysis involved several tests, including validity and reliability tests, classical assumption tests (normality, multicollinearity, heteroscedasticity, and autocorrelation), and hypothesis testing (t-test, F-test, and coefficient of determination). The results show that leadership style (X1) has a significant partial effect on performance (t = 3.618 t-table = 2.012), as does work discipline (X2) (t = 2.758 t-table = 2.012). Simultaneously, both variables significantly influence performance (F = 28.593 F-table = 3.195). The R Square value of 73.8% indicates a strong relationship, with most variation in performance explained by leadership style and work discipline.